High Detectivity Near Infrared Organic Photodetectors Using an Asymmetric Non-Fullerene Acceptor for Optimal Nanomorphology and Suppressed Dark Current - Ha, Jong Woon; Lee, Ah Young; Eun, Hyeong Ju; Kim, Jae Hyun; Ahn, Hyungju; Park, Sungjun; Lee, Changjin; Seo, Deok Won; Heo, Junseok; Yoon, Sung Cheol; Ko, Seo Jin; Kim, Jong H. (ACS Nano, 2023)
Recently, the development of non-fullerene acceptors (NFAs) for near-infrared (NIR) organic photodetectors (OPDs) has attracted great interest due to their excellent NIR light absorption properties. Herein, we developed NFAs by substituting an electron-donating moiety (branched alkoxy thiophene (BAT)) asymmetrically (YOR1) and symmetrically (YOR2) for the Y6 framework. YOR1 exhibited nanoscale phase separation in a film blended with PTB7-Th. Moreover, substituting the BAT unit effectively extended the absorption wavelengths of YOR1 over 1000 nm by efficient intramolecular charge transfer and extension of the conjugation length. Consequently, YOR1-OPD exhibited significantly reduced dark current and improved responsivity by simultaneously satisfying optimal nanomorphology and significant suppression of charge recombination, resulting in 1.98 × 1013 and 3.38 × 1012 Jones specific detectivity at 950 and 1000 nm, respectively. Moreover, we successfully demonstrated the application of YOR1-OPD in highly sensitive photoplethysmography sensors using NIR light. This study suggests a strategic approach for boosting the overall performance of NIR OPDs targeting a 1000 nm light signal using an all-in-one (optimal morphology, suppressed dark current, and extended NIR absorption wavelength) NFA.
Keywords: Asymmetric molecular structure; Intermolecular interactions; Nanomorphologies; Near Infrared; Near infrared light; Near infrared photodetectors; Near-infrared; Near-infrared absorbing non-fullerene acceptor; Organic near-infrared photodetector; Organics; asymmetric molecular structure; dark current; intermolecular interaction; near-infrared absorbing non-fullerene acceptors; organic near-infrared photodetectors